Role of multivalent Cu, oxygen vacancies and CuO nanophase in the ferromagnetic properties of ZnO:Cu thin films. Issue 69 (29th July 2015) - Younas, M.; Shen, Junying; He, Mingquan; Lortz, R.; Azad, Fahad; Akhtar, M. J.; Maqsood, A.; Ling, F. C. C.
<x xml:space="preserve">Abstract</x> Room temperature ferromagnetism (FM) of these thin film samples are highly tuneable by the simultaneous presence of CuO nanophases and multivalent Cu and Vö concentrations.